99.1k views
1 vote
3(e-3)-7(2e-8) - (e-1) =0​

2 Answers

4 votes
e = 4 if that’s what ur asking for
User Roland Schaer
by
5.9k points
5 votes

Answer:

e = 4

Explanation:

3 ( e - 3 ) - 7 ( 2e - 8 ) - ( e - 1 ) = 0

The first step to solving such an equation is to distribute. Multiply the term outside of the parentheis by every term inside of the parenthesis,

3e - 9 - 14e + 56 - e + 1 = 0

Simplify, combine like terms,

3e - 9 - 14e + 56 - e + 1 = 0

3e - 14e - e - 9 + 56 + 1 = 0

-12e + 48 = 0

Inverse operations,

-12e + 48 = 0

+12e +12e

48 = 12e

/12 /12

4 = e

User Wenlong Jiang
by
5.7k points